Developing (r,Q) & (R,T) inventory control models - Magsud Amiri; , Mohammad Amin Nayebi; Oveis Zarabadipour (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2014)
In this paper we have developed inventory control models (r,Q) & (R,T) in multi-items environment by two objectives as minimizing costs (holding & shortage) and risk level under four constraints. These constraints include: available budge, service level, storage space & allowed shortage quantities. Demand functions assumed normal in the study and extra demands also are backlogged. First we developed crisp models and then fuzzy stochastic models with fuzzy budge, allowed shortage quantities and shortage space which are fuzzy-stochastic parameters with normal distribution. All of fuzzy numbers are triangular typically. In this methodology we changed fuzzy-stochastic models to crisp multi objectives problem, by using difuzzification of fuzzy constraints and then solving by Fuzzy logic method. Finally we have tested an example to describe the model and methodology which is solved by LINGO package. .